Breaking the Grammar Barrier: Boosting EFL Motivation with Microlearning Videos - Sovia, Syahrini; Jamilah (Universitas Hamzanwadi, 2025)
Grammar learning in EFL settings is often seen as difficult because it involves abstract rules that need repeated practice and meaningful context to master. Many students lack motivation to learn grammar, which harms their ability to use grammatical structures correctly. Microlearning videos, which provide short, focused, visually engaging lessons, are effective in making grammar learning more accessible and motivating by offering contextualized examples and immediate reinforcement. Therefore, this study examined how well microlearning videos improve eighth-grade students’ motivation and grammar skills. A quasi-experimental pretest-posttest design was carried out at SMPIT Al-Masykar Bina Insani with 55 students (32 males, 23 females), divided into an experimental group (n=32, using microlearning videos) and a control group (n=23, using textbooks). Grammar tests (25 multiple-choice questions) and a motivation questionnaire (16 items measuring intrinsic and extrinsic motivation) were given and analyzed using SPSS 26.0 (descriptive statistics and MANOVA). Results showed significant differences between the groups in both grammar scores (M=69.13 vs 55.48, p<.05) and motivation levels. The experimental group experienced increased intrinsic motivation in communication, social, and skill areas, and higher extrinsic motivation in knowledge and achievement, while the control group’s motivation slightly decreased. These results suggest that microlearning videos are an effective alternative to traditional grammar teaching, supporting both language skills and motivation in EFL classrooms.